Tackling Intrinsic Antibiotic Resistance in Serratia marcescens with a Combination of Ampicillin/Sulbactam and Phage SALSA - Lorenz Weber; Mathias Jansen; Alex Krüttgen; Eva Miriam Buhl; Hans-Peter Horz (MDPI AG, 2020)
During the antibiotic crisis, bacteriophages (briefly phages) are increasingly considered as potential antimicrobial pillars for the treatment of infectious diseases. Apart from acquired drug resistance, treatment options are additionally hampered by intrinsic, chromosomal-encoded resistance. For instance, the chromosomal ampC gene encoding for the AmpC-type β-lactamases is typically present in a number of nosocomial pathogens, including S. marcescens. In this study, phage SALSA (vB_SmaP-SALSA), with lytic activity against clinical isolates of S. marcescens, was isolated from effluent. Besides phage characterization, the aim of this study was to evaluate whether a synergistic effect between the antibiotic ampicillin/sulbactam (SAM) and phage can be achieved despite intrinsic drug resistance. Phage SALSA belongs to the Podoviridae family and genome-wide treeing analysis groups this phage within the phylogenetic radiation of T7-like viruses. The genome of Phage SALSA consists of 39,933 bp, which encode for 49 open reading frames. Phage SALSA was able to productively lyse 5 out of 20 clinical isolates (25%). A bacterial challenge with phage alone in liquid medium revealed that an initial strong bacterial decline was followed by bacterial re-growth, indicating the emergence of phage resistance. In contrast, the combination of SAM and phage, together at various concentrations, caused a complete bacterial eradication, confirmed by absorbance measurements and the absence of colony forming units after plating. The data show that it is principally possible to tackle the axiomatic condition of intrinsic drug resistance with a dual antimicrobial approach, which could be extended to other clinically relevant bacteria.